APPLICABILITY ANALYSIS OF REST AND SOAP WEB SERVICES - Zientarski, Tomasz; Miłosz, Marek; Kamiński, Marek; Kołodziej, Maciej (Informatyka, Automatyka, Pomiary w Gospodarce i Ochronie Środowiska, 2017)
Web Services are common means to exchange data and information over the network. Web Services make themselves available over the Internet, where technology and platform are independent. These web services can be developed on the basis of two interaction styles such as Simple Object Access Protocol (SOAP) and Representational State Transfer Protocol (REST). In this study, a comparison of REST and SOAP web services is presented in terms of their applicability in diverse areas. It is concluded that in the past both technologies were equally popular, but during the rapid Internet development the REST technology has become the leading one in the area of access to Internet services.